Multiscale simulation approaches to modeling drug–protein binding. (April 2020) - Jagger, Benjamin R; Kochanek, Sarah E; Haldar, Susanta; Amaro, Rommie E; Mulholland, Adrian J
Highlights: Drug binding is inherently multiscale as it occurs over a broad range of length and time scales. Multiscale simulation methods combine molecular descriptions to access drug-relevant timescales, balancing detail and cost. Molecular descriptions can be linked to subcellular and cellular models to study more complex phenomena. Incorporation of experimental and structural data into integrative multiscale simulation methods holds great potential. Abstract : Simulations can provide detailed insight into the molecular processes involved in drug action, such as protein–ligand binding, and can therefore be a valuable tool for drug design and development. Processes with a large range of length and timescales may be involved, and understanding these different scales typically requires different types of simulation methodology. Ideally, simulations should be able to connect across scales, to analyze and predict how changes at one scale can influence another. Multiscale simulation methods, which combine different levels of treatment, are an emerging frontier with great potential in this area. Here we review multiscale frameworks of various types, and selected applications to biomolecular systems with a focus on drug–ligand binding.